RELIGIOUS HYBRIDITY: THE RESPONSE OF MUSLIM YOUTH TO TERAS DAKWAH COMMUNITY - Lubis, Muhammad Abdi (al-Balagh : Jurnal Dakwah dan Komunikasi, 2023)
Religious hybridity warrants complex study due to its profound impact in engaging young Muslims with dynamic religious perspectives. Teras Da'wah in Yogyakarta has become a notable contemporary religious community, merging cultural and religious elements in its da'wah practices. This research delves into the hybridization process within the Teras Dakwah community, aiming to bolster the enthusiasm of young Muslims. Employing ethnographic and netnographic approaches, the study investigates the specific type of hybridization that Teras Dakwah utilizes to captivate worshippers from diverse backgrounds. The findings in this research show that the hybridization carried out by the Yogyakarta Teras Dakwah community combines religious and cultural elements in the process of preaching. A hybrid identity can also be seen in the ustaz, which gives lectures from various groups. Additionally, a hybrid identity is evident among the ustaz who deliver lectures from multiple perspectives. Notably, the Teras Dakwah's 'Fun Koran' program is particularly popular among millennials, as it adeptly addresses, understands, and incorporates the turmoil and diverse inputs from congregants. This research suggests a significant shift in the da'wah activities of young Muslims in contemporary times, moving from traditional to more hybrid methods.